The Relationship Between Pet Attachment And Emotional Focused Coping Among College Students Who Own Cats - Salmaa Asmahan Fa'izah; Mustaqim Setyo Ariyanto (INDONESIAN COUNSELING AND PSYCHOLOGY, 2025)
Emotional focused coping in college students is influenced by several factors, one of which is external factors such as environmental conditions and the receipt of social support. This study aims to determine the relationship between pet attachment and emotional focused coping in college cat owners. The research method used is quantitative correlation using accidental sampling technique. The sample used by the researcher was 203 respondents who were college cat owners in Yogyakarta. Data collection used a pet attachment scale and emotional focused coping. Research data analysis used a product moment correlation test. The results of this study indicate that there is a relationship between pet attachment and emotional focused coping in college cat owners in Yogyakarta with a significant value (sig) of 0.001 (p <0.05) meaning that when the level of emotional focused coping increases, the level of pet attachment tends to decrease, or vice versa. These findings are expected to help readers understand how attachment patterns with pets influence students' emotional coping strategies in the modern era.